Early Identification of Olive Oil Defects throughout Shelf Life - Freitas, Flávia (2024)
Funding Information: This work received support and help from FCT/MCTES through national funds: Associate Laboratory for Green Chemistry—LAQV (LA/P/0008/2020 DOI 10.54499/LA/P/0008/2020, UIDP/50006/2020 DOI 10.54499/UIDP/50006/2020 and UIDB/50006/2020 DOI 10.54499/UIDB/50006/2020); MED—Mediterranean Institute for Agriculture, Environment and Development (UIDB/05183/2020 DOI 10.54499/UIDB/05183/2020 and UIDP/05183/2020 DOI 10.54499/UIDP/05183/2020); CHANGE-Global Change and Sustainability Institute (LA/P/0121/2020 DOI 10.54499/LA/P/0121/2020). This research was also anchored by the RESOLUTION LAB, an infrastructure at NOVA School of Science and Technology. This research was supported by National Funds through the FCT—Foundation for Science and Technology under the Ph.D. Grant of Flávia Freitas (2020.08089.BD DOI 10.54499/2020.08089.BD). Publisher Copyright: © 2024 by the authors.